THE EFFECT OF IMPLEMENTING CORPORATE GOVERNANCE ON FINANCIAL REPORTING FRAUD (EMPIRICAL STUDY OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2016-2021) - Purba, Nursiti Inka Kristi; Syafruddin, Muchamad (STIE Pelita Nusantara Semarang, 2023)
This study aims to explore the impact of corporate governance and its mechanisms in preventing companies from resorting to fraudulent financial reporting. The mechanism is based on eight corporate governance mechanisms, including board independence, board remuneration, managerial finance expertise, management industry expertise, board financial expertise, board industry expertise, board scope of effort and managerial ownership. For this purpose, using systematic random sampling, information from 40 companies listed on the Indonesia Stock Exchange (IDX) for six years from 2016 to 2021 was collected, and hypotheses were tested using a linear regression model. To measure fraudulent financial reporting, the Beneish-adjusted model was used to evaluate corporate governance. The mechanism used has been reviewed and calculated as a composite index of corporate governance. The findings indicate that strong corporate governance significantly reduces corporate intentions towards fraudulent financial reporting. A negative and significant relationship was observed between each of the eight corporate governance mechanisms, except for board remuneration which showed an insignificant positive relationship.